2011
DOI: 10.1097/bcr.0b013e31820334c7
|View full text |Cite
|
Sign up to set email alerts
|

Distraction Histogenesis in Ankle Burn Deformities

Abstract: Burn injuries involving the joints around the lower extremity often lead to debilitating postburn contractures that frequently compromise extremity functions. Treatment of such injuries, especially involving the ankle and foot area, is very challenging. Conservative management has limited efficiency in correcting the deformities, whereas open surgical treatment is often coupled with high complication rates because of poor soft-tissue coverage and poor vascularity around the burnt areas. The use of the Ilizarov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…Barquet et al specially designed an external fixator to gradually and slowly draw the flexion contracture of patients with knee stiffness, which resulted in satisfying effects [21]. Saghieh et al applied Ilizarov external fixation to solve skin ductility difficulty in three cases of burned ankle stiffness patients [22]. There were also reported external fixation and free flap combined applications for severely recurrent flexion joint stiffness [23].…”
Section: Discussionmentioning
confidence: 99%
“…Barquet et al specially designed an external fixator to gradually and slowly draw the flexion contracture of patients with knee stiffness, which resulted in satisfying effects [21]. Saghieh et al applied Ilizarov external fixation to solve skin ductility difficulty in three cases of burned ankle stiffness patients [22]. There were also reported external fixation and free flap combined applications for severely recurrent flexion joint stiffness [23].…”
Section: Discussionmentioning
confidence: 99%
“…van Roermund et al [4] observed a decrease in pain and improvement of joint function in 3 patients with ankle joint stiffness. Similarly, Said Saghieh et al [9] described their successful experience in treating severe PAC with Ilizarov technique in 3 patients.…”
Section: Treatment With External Xatormentioning
confidence: 99%
“…3,9,25,26,28,33 Such procedures are associated with a high risk of vascular and soft tissue complications, because deep scarring and retraction involving the posterior-medial neurovascular bundle of the foot and ankle from previous surgeries are common. 3,22,27,33 Arthrodesis with deformity correction usually involves extensive dissection of soft tissue, multiple osteotomies removal of large bone wedges, with increased risk of skin and bone necrosis and/or infection, 10,24,25,27 as well as excessive shortening of the foot and limb, leading to imbalance on the contralateral side. 2,3,5,20,25 Stiff equinovarus deformities (ECDs) of the foot are mostly caused by neglected trauma, 14,29 burns, 19,27 compartment syndrome of the leg, 5,14,16 peripheral nerve injury, 31 and central nervous system lesions.…”
Section: Introductionmentioning
confidence: 99%
“…3,22,27,33 Arthrodesis with deformity correction usually involves extensive dissection of soft tissue, multiple osteotomies removal of large bone wedges, with increased risk of skin and bone necrosis and/or infection, 10,24,25,27 as well as excessive shortening of the foot and limb, leading to imbalance on the contralateral side. 2,3,5,20,25 Stiff equinovarus deformities (ECDs) of the foot are mostly caused by neglected trauma, 14,29 burns, 19,27 compartment syndrome of the leg, 5,14,16 peripheral nerve injury, 31 and central nervous system lesions. 2,23,26,30 These cosmetically challenging and functionally incapacitating deformities are common in developing countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation